The Stellar Mass Fundamental Plane and Compact Quiescent Galaxies at z < 0.6 - Zahid, H. Jabran (2016)
We examine the evolution of the relation between stellar mass surface density, velocity dispersion, and half-light radius—the stellar mass fundamental plane (MFP)—for quiescent galaxies at z < 0.6. We measure the local relation from galaxies in the Sloan Digital Sky Survey and the intermediate redshift relation from ∼500 quiescent galaxies with stellar masses 10 ≲ log(M*/M⊙) ≲ 11.5. Nearly half of the quiescent galaxies in our intermediate redshift sample are compact. After accounting for important selection and systematic effects, the velocity dispersion distribution of galaxies at intermediate redshifts is similar to that of galaxies in the local universe. Galaxies at z < 0.6 appear to be smaller (≲0.1 dex) than galaxies in the local sample. The orientation of the stellar MFP is independent of redshift for massive quiescent galaxies at z < 0.6 and the zero-point evolves by ∼0.04 dex. Compact quiescent galaxies fall on the same relation as the extended objects. We confirm that compact quiescent galaxies are the tail of the size and mass distribution of the normal quiescent galaxy population.